Accounting for climate change - Kaplan, RS; Ramanna, K (Harvard Business School Publishing, 2021)
Corporations are facing growing pressure—from investors, advocacy groups, politicians, and even business leaders themselves—to reduce greenhouse gas (GHG) emissions from their operations and their supply and distribution chains. About 90% of the companies in the S&P 500 now issue some form of environmental, social, and governance report, almost always including an estimate of the company’s GHG emissions. The authors describe these as “catchall reports that are often made up of inaccurate, unverifiable, and contradictory data.” They propose a remedy: the E-liability accounting system, whereby emissions are measured using a combination of chemistry and engineering, and principles of cost accounting are applied to assign the emissions to individual outputs. The authors provide a detailed method for assigning E-liabilities across an entire value chain, using the example of a car-door manufacturer whose furthest-removed supplier is a mining company, which transfers its products to a shipping company, which transports them to a steel company, and so on until the car reaches the end customer.